(untitled) (Research, Society and Development, 2021)
In a gradual process of urbanization, American Tegumentary Leishmaniasis (ATL) is a worrying anthropozoonosis due to its seriousness and threat to public health. This study aimed to evaluate the incidence of ATL cases from 2014 to 2018 and to draw an epidemiological profile of the disease in the city of Teófilo Otoni - MG, using data: gender, age group, race, form of entry into the system, housing area and neighborhood, clinical forms presented, diagnostic method and medications used in the treatment. A total of 75 cases were reported in the period, with the brown race, male and 20-49 year-old population being the most affected. Clinical epidemiological diagnosis was performed in 52% of cases, the most prevalent clinical form was the cutaneous one, and the most common treatment was the first-line antimonial in Brazil. Since there were no studies of the disease in the city, this work can contribute to the epidemiological understanding of the disease in the region and thus contribute to taking more assertive measures for its control, and prevention.